Bacteriological and histopathological investigations of liver abscesses - K.F. Lechtenberg; H.W. Leipold; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1986)
Fusobacterium necrophorum was the predominant bacterial isolate from 49 liver abscesses. Biotype A tended to occur in pure infections and produced a more severe tissue reaction than biotype B, which tended to occur as a mixed infection.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Liver abscesses; Bacteria